Synergistic effects of nab-PTX and anti-PD-1 antibody combination against lung cancer by regulating the Pi3K/AKT pathway through the Serpinc1 gene - Zhang, Jun; Tang, Zhijia; Guo, Xi; Wang, Yunxia; Zhou, Yuhong; Cai, Weimin (Frontiers in Oncology, 2022)
Lung cancer is a type of cancer with higher morbidity and mortality. In spite of the impressive response rates of nab-paclitaxel (nab-PTX) or programmed cell death 1 (PD-1) and its ligand inhibitors, the effective treatment remains limited. Currently, alternative strategies aim at drug combination of nab-PTX and PD-1/PD-L1 inhibitors. Even as the clinical impact of the combined agents continues to increase, basic researches are still limited and the mechanisms underlying this synergy are not well studied. In this study we evaluated the antitumor efficacy and the molecular mechanisms of action of nab-PTX in combination with anti-PD-1 antibody, using Lewis lung carcinoma (LLC) cell and subcutaneously transplanted tumor models. Combination of nab-PTX and anti-PD-1 antibody displayed stronger antitumor effects, manifested at tumor growth, Ki67 and TUNEL staining. In vivo experiments showed significant increases in CD4+ T cells, CD8+ T cells, IFN-γ, TNF-α, IL-2, PF and Gzms-B, exerting anti-tumor effects with reductions in MDSCs and IL-10 after the treatments. Furthermore, transcriptomic analysis indicated twenty overlapped differentially expressed genes, and Serpin peptidase inhibitor clade C Member 1 (Serpinc1) was downregulated during treatment in vivo, whose expression level was markedly related to metastasis and overall survival of lung cancer patients. Functional enrichment analysis of the target gene revealed primary GO terms related to tumor, which warrants further investigation. We also found that Serpinc1 overexpression promoted cell proliferation, migration and invasion, and inhibited cell apoptosis of LLC cells in vitro, possibly regulating the associated factors via Pi3K/AKT pathway. In summary, our results reveal the synergistic anti-tumor responses of nab-PTX combined with anti-PD-1 antibody, in which Serpinc1 may play an important role, providing a target gene for combination treatment strategy.